2001
DOI: 10.1093/toxsci/61.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type Specific Differences in Glutamate Cysteine Ligase Transcriptional Regulation Demonstrate Independent Subunit Control

Abstract: Glutamate cysteine ligase (GCL; also referred to as gamma-glutamylcysteine synthetase, GCS) catalyzes the rate-limiting step of glutathione synthesis. The GCL holoenzyme is composed of a catalytic (GCLC; also called GCS(h)) and a modifier (GCLM; also called GCS(l)) subunit, each encoded by a unique gene. Wild-type and mutant promoter/luciferase reporter transgenes containing the promoter region of each GCL subunit gene were transfected into A549 (lung carcinoma), HEK 293 (transformed embryonic kidney), HepG2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 41 publications
2
17
0
1
Order By: Relevance
“…In MDBK cells, two GCLC transcripts of 4.1 kb and 3.2 kb were detected, consistent with results found for human GCLC (8). The Northern blot data show that BVDV infection caused a progressive decrease in both GCLC transcripts (Fig.…”
Section: Downregulation Of Bcl-2 Induction Of Chop/gadd153supporting
confidence: 89%
See 1 more Smart Citation
“…In MDBK cells, two GCLC transcripts of 4.1 kb and 3.2 kb were detected, consistent with results found for human GCLC (8). The Northern blot data show that BVDV infection caused a progressive decrease in both GCLC transcripts (Fig.…”
Section: Downregulation Of Bcl-2 Induction Of Chop/gadd153supporting
confidence: 89%
“…Consistent with this observation, BVDV infection led to a reduction in GCLC mRNA, the catalytic subunit of glutamate-cysteine ligase and the rate-limiting enzyme in glutathione biosynthesis (8). Concomitant with the loss of GCLC mRNA was a dramatic decrease in intracellular GSH levels which corresponded with the phenotypic onset of apoptosis seen at 20 to 25 h postinfection (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…The transcription of the GCLC gene was independently regulated and displayed cell-type specific differences in both basal and inducible conditions [Dahl and Mulcahy, 2001]. Our promoter analysis revealed that the proximal GC-rich region from À90 to À34 contained the cis-elements for transactivation of the GCLC gene in response to quercetin as well as for the maintenance of basal activity of the gene.…”
Section: Discussionmentioning
confidence: 80%
“…A proteína Keap1 contém resíduos conservados de cisteína, os quais desempenham um papel crí-tico na manutenção do Nrf2 no citoplasma. Entretanto, um aumento na produção de EROS no organismo promove no citoplasma a dissociação desse complexo, fazendo com que o Nrf2 fique ativado, sendo transportado para o núcleo (34,35). No núcleo das células, esse fator de transcrição se liga a elementos de resposta a antioxidantes (ARE) na região promotora dos genes que transcrevem enzimas antioxidantes endógenas.…”
Section: Discussionunclassified